PEMBENTUKAN KADER LAKTASI UNTUK MENINGKATKAN KETERAMPILAN MENYUSUI PADA IBU NIFAS - Wenny Indah Purnama Eka Sari; Yenni Puspita; Kurniyati Kurniyati (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2022)
Health cadres are at the forefront of community empowerment-based health sector development. The role of health practitioners in health development is very important. To increase the prevalence of exclusive breastfeeding, it is necessary to form cadres to support breastfeeding to support the development of family nutrition, especially exclusive breastfeeding. The purpose of this community service activity was to form Lactation Cadres through cadre training to improve the skills of breastfeeding mothers. The results of the pretest and posttest to determine the knowledge of cadres before and after lactation cadre training showed that there was an increase in knowledge of 20 points, meaning that all cadres had good knowledge. The average skill of the cadres during the practicum, namely the proper breastfeeding technique was 81,5, milking and storing breast milk was 82,5, oxytocin massage was 80 and lactation massage was 83,3. The average skill of cadres during mentoring, oxytocin massage was 90,8 and lactation massage was 92,3. The average breastfeeding skill of postpartum mothers who have been educated by lactation cadres, proper breastfeeding techniques was 91,6 and milking as well as storing breast milk was 88,9. This shows breastfeeding skills in the very good category. The Lactation Cadre of Kampung Delima Village, Rejang Lebong Regency, Bengkulu Province has been formed and has good knowledge and skills so that it can improve the skills of breastfeeding mothers. Lactation Cadres were appointed through a Decree of the Village Head of Kampung Delima which also contains a description of the main duties of the Lactation Cadres.